Live Communication: Events and visibility, key elements for the organizations - Rodríguez Gómez, Alfredo A. (Historia y Comunicación Social, 2014)
There is a growing desire of institutions to communicate through events as a way to directly access the audience, in a model that includes communication skills, marketing and event management. Joining these techniques is therefore a very current exercise for a live communication. In this paper we report a discussion of the use of current technology as a tool for the live communication, as long as it use in all phases of an event: preparation, event itself and post-event.